Motilitas Spermatozoa Ayam (Galus varius) Pada Penyimpanan Dingin Dengan Pengencer Tris, Cytrate, Kuning Telur, Filtrat Jambu Biji (Psidium guajava) Dan Buah Tin (Fikus karika rob) - Lukman H.Y.; Sumadiasya I.W.L.; Adji Santoso Dradjat (Faculty of Animal Husbandry, University of Mataram, 2018)
The objectives of this study were to evaluate rooster semen preserved using Tris Citrate Egg Yolk-Citrate (TEYC) extender with the addition of Tin fruit and guava filtrate. Semen was collected by using plastic collector placed on cloaca, by using hen as a teaser when rooster mated hen consequently semen would remain in the plastic collector. Fresh semen was evaluated by evaluating volume, smell, color and spermatozoa concentration. Then semen was split into 7 fractions as treatment 1, 2 and 3 were extended 10 times using TEYC with 20%, 25% and 30% egg yolk. Then treatment 4 and 5 were extended using TEYC contain 20% egg yolk with 5 % and 10% guava filtrate. Treatments 6 and 7, were extended using TECY contain 20% egg yolk with Tin fruit filtrate of 5 and 10%. Then preserved and progressive motility was evaluated at 0, 12, 24 and 36 hours following chilling under 4°C. Results showed that ejaculate volume was 0.38 ± 0.14 ml, specific smell, milky white color with concentrations of 511.00 ± 90.07 x 107 sperms/ml. The results of progressive motility evaluation of 0, 12, 24 and 36 hours following chilling treatments 1 to 7 were not significantly different (P> 0,05). Percentage motility of chilling 0 hours and 36 hours of treatments 1 to 7, were from 86.50 ±4.72% to 48.83 ±5.15%, from 83.83 ±7.41% to 47.83 ±7.44%, from 88.67 ±1.86% to 49.33 ±9.35%, from 83.00 ±4.69 % to 43.50 ±7.77%, from 82.67 ± 6.06%, to 46.33 ±5.75%, from 83.83 ±7.41% to 47.83 ±7.44%, from 88.67 ±1.86% to 49.33 ±9.35% respectively and the average decreasing progressive motility up to 36 hours was 37.74 ± 1.64 %. Finally, it can be concluded that addition egg yolk, guava, and Tin fruit filtrate do not influence the progressive motility of local rooster spermatozoa.